Why Does Disability Insurance Enrollment Increase During Recessions? Evidence from Medicare - Carey, Colleen; Miller, Nolan; Molitor, David (The Review of Economics and Statistics, 2026)
Social Security Disability Insurance (DI) awards rise in recessions, especially for workers over age 50. We use Medicare data to investigate how health, entry costs, and age-based DI eligibility rules shape this pattern. Entrants induced by recessions have lower medical spending and mortality than typical recipients. Entry responses to unemployment jump two- to fourfold at ages 50 and 55, when eligibility rules relax. Using these age-based discontinuities as instruments, we find no shift in marginal entrants' health across unemployment levels. These findings show that DI's age-based eligibility rules are a primary driver of cyclical entry, while health shocks are not.